Complexity of comprehensive care treatments in undergraduate dental programs: The benefits of observing and assisting experienced faculty members - Moataz Elgezawi; Khalid Hassan; Adel Alagl; Ahmad M. Al-Thobity; Basel Al-Mutairi; Thamir Al-Houtan; Shazia Sadaf (Saudi Dental Journal)
Objective: To improve the confidence of the final year dental students in completing occlusal and oral rehabilitation of patients, with complexities beyond their scope, based on full analysis of the biomechanical and esthetic considerations of each case. Material & methods: Two comprehensive patient situations presenting with special difficulties including extensive, reduced vertical dimension of occlusion, limited interocclusal space and maxillary alveolar bone for implant insertion necessitating bone augmentation and a sinus lift surgery was managed by two students at our institute. Procedures like surgical crown lengthening, sinus lifting, and bone augmentation were performed by senior faculty with the respective two students’ assisting as well as following up at the healing phase and reporting progress of healing and any possible complications to the supervisor. Students’ reported significant improvement in decision making skills; time management; interpersonal skills, management of cases in an evidence –based interdisciplinary approach as well as increase in their confidence in managing complex cases independently. Follow up with both cases showed optimum outcome and patients’ satisfaction. Results: Students’ reported significant improvement in decision making skills; time management; interpersonal skills, management of cases in an evidence –based interdisciplinary approach as well as increase in their confidence in managing complex cases independently. Follow up with both cases showed optimum outcome and patients’ satisfaction. Conclusions: Exposing students to manage complex oral rehabilitation including procedures like sinus lifting and bone augmentation, through an evidence-based interdisciplinary approach during the undergraduate comprehensive clinical dentistry course enhances their confidence and clinical acumen as an independent practitioner. Keywords: Comprehensive dentistry, Case report, Occlusal and oral rehabilitation, Interdisciplinary management, Undergraduate student